Destination vs event attributes: Enduring spectators' loyalty. Issue 5 (20th October 2019) - Kruger, Martinette; Viljoen, Armand
Abstract: Endurance athletes need social and emotional support from family and friends, who act as spectators at the event in which they participate. Although spectators fulfill a supportive role, does their loyalty lie with the event, the event destination or a combination of both? The case study was the Ironman Triathlon hosted in South African cities. Questionnaires were distributed to spectators on the race days, and 748 completed questionnaires were obtained. Three factor analyses were performed on the spectators' travel motives, perception of destination attributes and perception of sport event attributes. Linear regression analyses were performed with event loyalty as the dependent variable, whereas the remaining motives, dimensions and attributes were the independent variables. The results revealed that a combination of factors was statistically significant and that a different set of determinants were observed for the two events. The results revealed that sport event organizers and destination management organizations should make use of both the event and the host destination attributes as drawing cards and act with local tourism and travel organizations to offer spectators a reduced fee for tourism offerings at the destination.